The Structure of Constitutional and Legal Institutions and their Impact on Political Leadership and Peacebuilding in Iraq - Al-Rubaie, Shahad Ghaleb; Omran, Omar Juma (Journal of Ecohumanism, 2025)
Political leadership has significant importance and a vital role in the conduct of public affairs and the management of institutions within the political system, in addition to its importance and weight in the political decision-making of countries, after which it is the most important variables affecting the political system. The role of political leadership is highlighted in determining the strength and status of the state through its performance in employing the elements of power. The material and human state, directly or indirectly, in building stability, development effectiveness, and progress. In addition to this importance, the study took a specific topic related to explaining the structure of constitutional and legal institutions and their impact on political leadership and achieving peace as their most essential functions in society.